Sex and age differences in the achievement of control targets in patients with type 2 diabetes: results from a population-based study in a South European region. Issue 1 (December 2016) - Cambra, K.; Galbete, A.; Forga, L.; Lecea, O.; Ariz, M.; Moreno-Iribas, C.; Aizpuru, F.; Ibañez, B.
Abstract Background We aimed to determine the degree to which control targets of glycaemia and cardiovascular risk factors were achieved among patients with type 2 diabetes and to investigate sex- and age-related differences in this population. Methods This cross-sectional, population-based study was conducted in Spain. Glycated hemoglobin (HbA1c), blood pressure, LDL-c, HDL-c, triglycerides, BMI, and smoking history were obtained from electronic clinical primary care records (n = 32, 638 cases). The proportions of patients who met control targets were determined according to sex and age groups. Comparisons between groups were conducted with t-tests for continuous variables, tests for trends in proportions for categorical and ordinal variables, and Pearson's chi-square tests and binary logistic regression models for categorical variables. Results The overall proportions of patients with type 2 diabetes who met the target objectives for HbA1c (<7 %, 53 mmol/mol), blood pressure (130/80 mmHg), and LDL-cholesterol (100 mg/dl) were 60, 40 and 41 %, respectively. Women were less likely than men to meet the control targets of HbA1c (59 vs 61 %), LDL (35 vs 45 %), and HDL (58 vs 78 %). Patients under 65 years of age presented poorer control than older age groups. Only a minority of patients with type 2 diabetes met the composite target objectives for glycemic control, blood pressure, and LDL. Conclusions There are differential gaps in the control results of female patients and younger patients, which should prompt improvements in case management and care. There is room for further improvement in the cardiometabolic control of patients with type 2 diabetes.